The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/s0014479722000023
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost seed storage technologies for development impact of small-scale seed saving entities in tropical climates

Abstract: Summary Seeds can deteriorate rapidly under high heat and humidity, making it challenging and potentially costly to store orthodox seeds effectively in the tropics, thereby affecting agriculture development. This work explores the effectiveness of novel, low-cost technologies for storing seeds in warm, humid, resource-constrained environments, focusing on maintaining the viability of seeds already dry prior to storage. Seeds of okra (Abelmoschus esculentus (L.) Moench), sorghum (Sorghum bicolor (L.) Moench)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Conservation of seeds is the primary method of choice when attempting to preserve the gene pool of a plant species [ 20 , 30 , 33 , 34 , 35 , 36 ]; therefore, deterioration of seeds during storage has profound influences on agriculture and conservation efforts [ 37 ]. Seed aging processes resulting in viability decline and final decrease of plantlet amount are dependent on storage conditions, which are the temperature and RH that determine seed MC.…”
Section: Discussionmentioning
confidence: 99%
“…Conservation of seeds is the primary method of choice when attempting to preserve the gene pool of a plant species [ 20 , 30 , 33 , 34 , 35 , 36 ]; therefore, deterioration of seeds during storage has profound influences on agriculture and conservation efforts [ 37 ]. Seed aging processes resulting in viability decline and final decrease of plantlet amount are dependent on storage conditions, which are the temperature and RH that determine seed MC.…”
Section: Discussionmentioning
confidence: 99%
“…Innovative drying techniques, such as low-energy methods, are necessary for reducing seed moisture to levels suitable for long-term storage. Trail et al (2021) found that storing seeds in dry, cool, and low-oxygen conditions slows seed metabolism, prolonging storage life. The significance of low-cost technologies for drying seeds is highlighted, particularly in tropical environments where high humidity and heat pose significant challenges to seed storage.…”
Section: Low-energy Drying Methodsmentioning
confidence: 99%
“…These methods help maintain seed quality by creating an environment that minimizes oxygen and moisture levels. The use of desiccants and vacuum sealing has also been proposed to maintain seed quality in climate-controlled seed banks (Trail et al, 2021).…”
Section: Vacuum-sealing and Controlled Atmosphere Storagementioning
confidence: 99%
“…At the time of storage, humidity, temperature, and the proportion of oxygen are the main environmental factors that influence seed deterioration [9]. Storing seeds longer than 1 year becomes a challenge even where seeds are saved, stored, and planted on short annual cycles [10].…”
Section: Introductionmentioning
confidence: 99%